TEACHING READING COMPREHENSION OF NARRATIVE TEXT USING STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Rini Nuraini; Mundriyah Mundriyah (PROJECT (Professional Journal of English Education), 2021)
Reading is an activity to obtain information from a text. Reading a text is not easy, it requires an understanding to get a meaning. The objective of the research was to identify the implementation of the scenario in teaching reading comprehension of narrative text using the Student Team Achievement Division and to find out students’ responses. The researcher used a descriptive qualitative method. The subject of this research was tenth-grade students of Vocational High School in Cimahi. The data were collected by using observation, questionnaires, and documents. The results of the research were the implementation of STAD in teaching reading comprehension was appropriated with the learning scenario. In the implementation of STAD in teaching reading comprehension of narrative text got a good response from students. By using STAD on English study could increase students' reading comprehension, students were motivated and involved in the active learning process. In addition, students felt learning was fun and not boring. STAD (Student Team Achievement Division) was suitable in teaching reading comprehension of narrative text at the tenth-grade students. The students understood better in reading comprehension using STAD. Keywords:  Reading Comprehension, Narrative Text, STAD